ANALISIS PEMECAHAN OVERSUPPLY BAWANG MERAH: KASUS BREBES - Henny Sukesi; Ninuk Rahayuningrum; Tjahya Widyanti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
The Onion is a seasional agro product, so it can causes supply fluctuations. While the demand are likely to remain. This condition affect to the fluctuation of onion prices in consumers’ level, while prices at the farmers' level are likely to remain low, even too low at the time of harvest. Lately, onion’ farmers also havíng pressure from onion importation that declining the price at farmers level, beside of the over supply. This over supply needs to be solved through (1) trade arrangements, (2) a warehouse system to get the best price, (3) post-harvest processing, (4) the development of onion processing industry (fried onion, onion flour, onion oil).